The Finance Circulation Control Through Green Interest Rates in Indonesia - Basmar, Edwin; Hasan, Hasan; Takhim, Muhamad; Pratiwi, Ratih (AKSES: Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the magnitude of interest rates influence on the financial cycle movement in Indonesia, green interest rates pressure is measured by the development of the Ed Waves Index measurement model, through Bank Indonesia Financial Report data from 1950 to 2020 on a quarterly basis. This research novelty because this research is a the development of a model in measuring the financial cycle in Indonesia, the research process was carried out by filtering one of the macroeconomic variables that formed the pre-existing financial cycle wave. This study results indicate that green interest rates pressures will have a strong influence on the financial cycle wave from + 3.7 Amplitudo to - 1.5 Amplitudo, when the financial cycle wave tends to weaken. This also applies to the opposite in the period of economic growth activity in Indonesia.